2022
DOI: 10.1021/acs.nanolett.2c00458
|View full text |Cite
|
Sign up to set email alerts
|

Spectrally Resolved Single Particle Photoluminescence Microscopy Reveals Heterogeneous Photocorrosion Activity of Cuprous Oxide Microcrystals

Abstract: Photocorrosion of cuprous oxide (Cu2O) has notably limited its application as an efficient photocatalyst. We report a facile approach to visualize in situ formation of copper and oxygen vacancies on the Cu2O surface under ambient condition. By imaging photoexcited single Cu2O particles, the resultant photoluminescence generated at Cu2O surface enable effective localization of copper and oxygen vacancies. Single particle photoluminescence imaging showed substantial heterogeneity in the rate of defect formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Another study also utilized single-particle photoluminescence microscopy to investigate defects, revealing heteroge-neous photocorrosion activity on Cu 2 O. 49 The emission of photoluminescence photons at 615, 710, 820, and 900 nm arises from distinct recombination processes involving photoexcited electrons, valence band holes, and vacancies in Cu 2 O. Specifically, the 615 nm emission results from electron−hole recombination in the bands, the 710 and 820 nm emissions arise from doubly ionized (VO 2+ ) and singly ionized (VO + ) oxygen vacancies, and the 900 nm emission stems from copper vacancies (V Cu ).…”
Section: Spatially Resolved Photoluminescence Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study also utilized single-particle photoluminescence microscopy to investigate defects, revealing heteroge-neous photocorrosion activity on Cu 2 O. 49 The emission of photoluminescence photons at 615, 710, 820, and 900 nm arises from distinct recombination processes involving photoexcited electrons, valence band holes, and vacancies in Cu 2 O. Specifically, the 615 nm emission results from electron−hole recombination in the bands, the 710 and 820 nm emissions arise from doubly ionized (VO 2+ ) and singly ionized (VO + ) oxygen vacancies, and the 900 nm emission stems from copper vacancies (V Cu ).…”
Section: Spatially Resolved Photoluminescence Mappingmentioning
confidence: 99%
“…Another study also utilized single-particle photoluminescence microscopy to investigate defects, revealing heterogeneous photocorrosion activity on Cu 2 O . The emission of photoluminescence photons at 615, 710, 820, and 900 nm arises from distinct recombination processes involving photoexcited electrons, valence band holes, and vacancies in Cu 2 O.…”
Section: Operando Functional Imaging To Monitor the Local Structure–r...mentioning
confidence: 99%
“…131 Likewise, single-particle PL microscopy has been reported for investigating the defects of single Cu 2 O microcrystals, revealing their corresponding heterogeneous photocorrosion activity (Figure 7c, d). 132 Understanding the photogenerated hole and electron pair behavior, photocatalytic active sites, and reaction processes on a single particle (catalyst) level is promising for developing efficient catalysts. In particular, titanium oxide (TiO 2 ) with various morphologies and different crystal structures has been documented as a powerful photocatalyst for diverse catalytic processes due to its high reactivity, nontoxicity, and chemical stability.…”
Section: Single Particle Photo(electro)catalysismentioning
confidence: 99%
“…(c, d) PL images of single Cu 2 O microcrystals over different periods of time for revealing their corresponding heterogeneous photocorrosion activity. Reprinted from ref from American Chemical Society, copyright 2022, .…”
Section: Single Particle Detection/imagingmentioning
confidence: 99%
“…27,28 However, the charge separation capability of Cu 2 O is poor, which strongly limits its solar energy conversion efficiencies and further potential applications. 29,30 It has been reported that Cu 2 O crystals with different exposed facets show various photocatalytic performances, [31][32][33] for instance, cubic Cu 2 O with {100} facets shows a lower performance in photocatalytic H 2 evolution than rhombic dodecahedral Cu 2 O with {110} facets. 34 In addition, {100} and {110} facets were considered more unstable than the {111} facet under a photocatalytic process.…”
Section: Introductionmentioning
confidence: 99%